Civil Liability of Legal Entities of Public Law - Amirkhanyan, S. (Bulletin of Yerevan University C: Jurisprudence, 2019)
Legislation of RA de facto establishes the structure of legal entities of public law, indicating that communities and inter-communal unions are legal entities of public law. However, the author finds that the types of legal entities of public law are not limited to this and include municipal institutions, the Central Bank of Armenia, public institutions and non-profit organizations. The article is devoted to the study of civil liability of legal entities of public law on the basis of Armenian, foreign law, as well as case law of the ECHR.